Misperceiving economic success: Experimental evidence on meritocratic beliefs and inequality acceptance - Dietmar Fehr; Martin Vollmann (University of Heidelberg, Department of Economics, 2020)
Most people tend to equate success with merit, a tendency that is particularly pronounced among conservatives. However, in practice it is exceedingly difficult to discern the relative impact of luck and effort to economic success. Based on a large-scale online study that samples the general US population, we investigate whether individuals misperceive the importance of luck for success, and how this mediates their meritocratic beliefs and acceptance of inequality. We randomly assign participants in pairs to compete in an easy or hard work assignment. The tasks are structured such that working on the easy work assignment almost certainly results in better performance and economic success. We show that economically successful participants overweight the role of effort in their success, perceiving high income as more deserved than unsuccessful participants. Subsequently, they demand less redistributive taxation, and they also show little interest in receiving information about the true determinants of their success. These general findings hold true regardless of political orientation. Successful liberals are as meritocratic as conservatives are, sharing the same beliefs in deservingness and preferences for low redistributive taxes.
urn:nbn:de:bsz:16-heidok-290719
Keywords: C93; D63; 330; inequality; fairness; deservedness; political views; cognitive dissonance